THE EFFECT OF PROBLEM-BASED LEARNING MODEL IN INFORMATION TECHNOLOGY INTERVENTION ON COMMUNICATION SKILLS - Lufri Lufri; Sintia Elmanazifa; Azwir Anhar (Ta'dib, 2021)
Communication skills need to be improved during learning. However, the learning process in schools has not fully implemented learning models that can improve students' communication skills. Learning in schools is still teacher-centered, lack of use of Information Technology (IT), students’ inactivity, and their lack of interest in learning in class. The solution is to apply the PBL learning model in IT interventions. The research objective was to develop students' communication skills. The instrument used is was a rubric to assess communication that had been validated by experts. The research design was Randomized Control Group Posttest Only Design. This type of research is a quasi-experimental. The data were analyzed by using  the two-way ANOVA test. The results showed that there was a significant difference between the PBL learning model and the information technology intervention on the communication skills of students with an average score of 64.27% in the experimental class and 57.70% in the control class and a significant value of 0.00